PRODUCTIVITY AND GENETIC DIVERSITY OF LOCAL CATTLE IN CIAMIS-WEST JAVA - Hilmia, N.; Noor, R.R.; Sumantri, C.; Gurnadi, R.E.; Priyanto, R. (Diponegoro University, 2013)
The objectives of this study were to identify the productivity and genetic diversity of local cattle inCiamis West Java based on DNA microsatellite, in order to provide the basic information for its rearing,conservation and development. Eighteen of local cattle were kept for 58 days by feeding concentratesand rice straw. The measured parameters were weekly body weight as well as carcass percentage. Thepercentage of comparing carcass was taken from PO, Bali and crossbred cattle from local cattle withLimousin, Simmental, Brahman and Angus cattle. Data were analyzed using Excel software and SAS(2004). Blood samples were taken from two subpopulations i.e., 46 and 52 samples from Tambaksariand Cijulang areas, respectively. Other DNA samples were collected from Bali, PO, Limousin, Simental,Brahman and Angus cattle. Genetic diversity and phylogenetic analysis were analyzed using 3microsatellite loci, that were INRA35, HEL9 and BM2113. The genotyping data were analyzed usingPOPGENE.32 program, while phylogenetic trees were analyzed by MEGA 4. Average daily gain (ADG)of local cattle in Ciamis was 0.62±0.23 kg/head/day with a carcass percentage was 51.62±1.80%. Thecarcasses percentage of local cattle in Ciamis was not significantly different from those of Bali, PO, andcrossbred cattle. The genetic diversity of local cattle in Ciamis was categorized in the medium level, thediversity of local cattle in Tambaksari subpopulation was higher than in Cijulang subpopulation. Localcattle in Ciamis had a closer genetic distance with the PO cattle.